Databook of blowing and auxiliary agents - Wypych, George (ChemTec Publishing, 2022)
Databook of Blowing and Auxiliary Agents, Second Edition includes the most current information on foaming technology, guiding users on the proper selection of formulation, which is highly dependent on the mechanisms of action of blowing agents and foaming agents, as well as dispersion and solubility. The book includes properties of 23 groups of blowing agents and the typical range of technical performance for each group, including general properties, physical-chemical properties, health and safety, environmental impact, and applications in different products and polymers. All information is illustrated by chemical reactions and diagrams. Chapters in the book look at foaming mechanisms with the use of solid blowing agents, which are decomposed to the gaseous products by application of heat, production of gaseous products by chemical reaction, and foaming by gases and evaporating liquids.